Study of Smart Microgrid Technology on a Laboratory Scale Grid System - Heri Suyanto; Erlina (ZETROEM, 2026)
The utilization of renewable energy sources to meet electricity demand has become increasingly important. However, comparative studies on the technical and economic performance of on-grid and off-grid smart microgrid systems remain limited. This study aims to evaluate the configuration and performance of a smart microgrid system by comparing different operating configurations using HOMER software. The system was modeled by defining the electrical load, simulating the proposed configurations, and evaluating their technical and economic performance based on power output, Net Present Cost (NPC), and Cost of Energy (COE). The results show that the proposed grid-connected smart microgrid provides the best overall performance, with approximately 80% of the electrical energy demand supplied by the photovoltaic (PV) system and the remaining 20% provided by the PLN grid, demonstrating effective utilization of renewable energy resources. Economically, the proposed system achieves an NPC of Rp. 828,391,700 and a COE of Rp. 419.28, which are lower than those of the off-grid configuration (NPC of Rp. 2,664,679,000 and COE of Rp. 3,151.07) and the grid-only configuration (NPC of Rp. 906,104,800 and COE of Rp. 1,071.00). These findings indicate that integrating photovoltaic generation with the utility grid offers a more cost-effective and reliable solution while significantly increasing the contribution of renewable energy to the electricity supply. Therefore, the proposed smart microgrid configuration can serve as a practical reference for the design and economic evaluation of future grid-connected renewable energy systems.